Pengaruh Dysmenorrhea Exercise Terhadap Intensitas Nyeri Haid Pada Remaja Putri Di SMP Negeri 1 Sitiung Kabupaten Dharmasraya Tahun 2023 - Lestari, Tri; Khotimah, Siti; Yuliawati, Eni (Bunda Edu-Midwifery Journal (BEMJ), 2023)
In Indonesia, the incidence of dysmenorrhea is quite large, reaching 60-70% of women in Indonesia. Gymnastics is a way that can be done to reduce dysmenorrhea. The general objective of this study was to determine whether there was an effect of dysmenorrhea exercise on the intensity of menstrual pain in female adolescents at SMP Negeri 1 Sitiung. In this study the experimental method was used in one group (one group pre test post test). The data analysis used was the Wilcoxon Signed Rank Test through the SPSS application. The results of this study showed that there was an effect of reducing pain levels after doing Dysmenorrhea exercises with a p-value of 0.05. It was concluded that most young women at SMP Negeri 1 Sitiung experienced a decrease in pain from severe to mild after doing dysmenorrhea exercises.